Contribution of the basal forebrain to corticocortical network interactions - Gombkoto, Peter (Brain Struct Funct, 2021)
Basal forebrain (BF) cholinergic neurons provide the cerebral cortex with acetylcholine. Despite the long-established involvement of these cells in sensory processing, attention, and memory, the mechanisms by which cholinergic signaling regulates cognitive processes remain elusive. In this study, we recorded spiking and local field potential data simultaneously from several locations in the BF, and sites in the orbitofrontal and visual cortex in transgenic ChAT-Cre rats performing a visual discrimination task. We observed distinct differences in the fine spatial distributions of gamma coherence values between specific basalo-cortical and cortico-cortical sites that shifted across task phases. Additionally, cholinergic firing induced spatial changes in cortical gamma power, and optogenetic activation of BF increased coherence between specific cortico-cortical sites, suggesting that the cholinergic system contributes to selective modulation of cortico-cortical circuits. Furthermore, the results suggest that cells in specific BF locations are dynamically recruited across behavioral epochs to coordinate interregional cortical processes underlying cognition. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00429-021-02290-z.